Exploring Vitamin B1 Cycling and Its Connections to the Microbial Community in the North Atlantic Ocean - Suffridge, Christopher P.; Bolaños, Luis M.; Bergauer, Kristin; Worden, Alexandra Z.; Morré, Jeff; Behrenfeld, Michael J.; Giovannoni, Stephen J. (Frontiers in Marine Science, 2020)
Vitamin B1 (thiamin) is an essential coenzyme for all cells. Recent findings from experimental cell biology and genome surveys have shown that thiamin cycling by plankton is far more complex than was previously understood. Many plankton cells cannot produce thiamin (are auxotrophic) and obligately require an exogenous source of thiamin or one or more of 5 different thiamin-related compounds (TRCs). Despite this emerging evidence for the evolution among plankton of complex interactions related to thiamin, the influence of TRCs on plankton community structure and productivity are not understood. We report measurements of three dissolved TRCs 4-amino-5-aminomethyl-2-methylpyrimidine (AmMP), 5-(2-hydroxyethyl)-4-methyl-1,3-thiazole- 2-carboxylic acid (cHET) and 4-methyl-5-thiazoleethanol (HET) that have never before been assayed in seawater. Here we characterize them alongside other TRCs that were measured previously (thiamin and 4-amino-5-hydroxymethyl-2-methylpyrimidine (HMP)), in depth profiles from a latitudinal transect in the north Atlantic in March 2018. TRC concentrations ranged from femptomolar to picomolar. Surface depletion relative to a maximum near the bottom of the euphotic zone and low concentrations at deeper depths were consistent features. Our observations suggest that when net plankton community production is low, TRC concentrations approach a steady state where TRC production and consumption terms are balanced. Standing stocks of TRCs also appear to be positively correlated with net productivity. However, near the period of peak biomass in the accumulation phase of a bloom we observed an inverse relationship between TRCs and bacterial production, coincident with an increased abundance of Flavobacteria that comparative genomics indicates could be vitamin B1 auxotrophs. These observations suggest that the dissolved pool of TRCs is often at steady state, with TRC production and consumption balanced. Our data suggests that bloom induced shifts in microbial community structure and activity may cause a decoupling between TRC production and consumption, leading to increased abundances of some populations of bacteria that are putatively vitamin B1 auxotrophs.